2011
DOI: 10.4314/ajpsy.v14i5.5
|View full text |Cite
|
Sign up to set email alerts
|

Profile of clinically-diagnosed dementias in a neuropsychiatric practice in Abeokuta, South-Western Nigeria

Abstract: Objective: Many subjects with dementia present primarily to neuropsychiatric practices because of behavioural and psychological symptoms (BPSD). This study reviewed the profile of clinically-diagnosed dementias and BPSD seen in a pioneer neuropsychiatric practice in Abeokuta, southwestern Nigeria over a ten year period (January1998 -December 2007). Methods: A review of hospital records of all patients with diagnoses of dementia or dementing illness using the ICD-10 criteria as well as specific diagnostic crite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(42 citation statements)
references
References 32 publications
2
38
2
Order By: Relevance
“…In the present study by using NPI-Q most common BPSD found was apathy (88%), followed by irritability (66%), appetite and change in eating pattern (57%). The findings are consistent with the studies performed earlier 11,12 In our study night time behaviour changes i.e. night time awakening, inability to sleep in night with frequent wandering and early morning awakening were also common.…”
Section: Discussionsupporting
confidence: 93%
“…In the present study by using NPI-Q most common BPSD found was apathy (88%), followed by irritability (66%), appetite and change in eating pattern (57%). The findings are consistent with the studies performed earlier 11,12 In our study night time behaviour changes i.e. night time awakening, inability to sleep in night with frequent wandering and early morning awakening were also common.…”
Section: Discussionsupporting
confidence: 93%
“…The reported prevalence of dementia for hospital-based studies ranged from 0.05% at a neuropsychiatric practice in southwestern Nigeria (survey period 1998–2007) [45], to 8.87% at a geriatric center in Dakar, Senegal [51]. Further, dementia accounted for 6.90% of patients with acute confusional state in a hospital in Tanzania [48], while 74.00% of 305 patients who presented to a memory clinic in South Africa were diagnosed with dementia [53].…”
Section: Resultsmentioning
confidence: 99%
“…However, few data on the prevalence and presentation of BPS in SSA exist. The only other data from SSA were also collected in Nigeria and suggested that BPS were at least as common as reported in HICs (Amoo et al, 2011;Baiyewu et al, 2003;Baiyewu et al, 2012;Hendrie et al, 2000). The only other data from SSA were also collected in Nigeria and suggested that BPS were at least as common as reported in HICs (Amoo et al, 2011;Baiyewu et al, 2003;Baiyewu et al, 2012;Hendrie et al, 2000).…”
Section: Introductionmentioning
confidence: 99%